Social Theory after the Internet : Media, Technology, and Globalization - Schroeder, Ralph (Knowledge Unlatched Select 2017 (on order), 2018)
"Social Theory after the Internet focuses on everyday uses and effects of the internet, including information seeking and big data, and explains how the internet has gone beyond traditional media in, for example, enabling Donald Trump and Narendra Modi to come to power. Schroeder puts forward a sophisticated theory of the role internet plays, and how both technological and social forces shape its significance. He provides a sweeping and penetrating study, theoretically ambitious and at the same time always empirically grounded"--Page 4 of cover